Increased risk for metachronous gastric adenocarcinoma following gastric MALT lymphoma—A US population‐based study. Issue 4 (1st June 2017) - Palmela, Carolina; Fonseca, Cristina; Faria, Rita; Baptista, Rute Baeta; Ribeiro, Sofia; Ferreira, Alexandre Oliveira
Abstract : Background: Gastric mucosa‐associated lymphoid tissue lymphoma (gMALT) and gastric adenocarcinoma (GC) are long‐term complications of chronic Helicobacter pylori (HP) gastritis. Treatment of HP infection induces remission in most patients with gMALT. Endoscopic follow‐up is not currently endorsed after complete remission. However, the risk of GC in these patients is unclear. Objective: The objective of this study is to estimate GC risk in gMALT patients. Methods: The National Cancer Institute Surveillance, Epidemiology and End Results 13 (SEER) database‐Nov 2014 Sub (1992–2012) was used to identify adult patients diagnosed with gMALT between 1992 and 2012. The standardized incidence ratio of second primary GC after a latency period of 12 months was calculated and compared to a reference SEER cohort of identical age, sex and time period. The risk of GC in these patients was also stratified by latency period (five years) and age. Results: We identified 2195 cases of gMALT lymphoma, and 20 (0.91%) of them subsequently developed GC with a relative risk (RR) of 4.32 (95% CI 2.64–6.67) compared to the American population. The median latency time was five years and the risk was maintained afterward (RR 4.92, 95% CI 2.45–8.79). When stratified by age group the risk was highest for the 45–64 group (RR 14.04, 95% CI 5.64–28.93). Conclusion: gMALT lymphoma is associated with an increased risk of metachronous gastric adenocarcinoma. The risk is still present after more than five years of follow‐up. Further studies may clarify the most adequate follow‐up strategy.